MULTITEMPORAL ANALYSIS OF THE URBAN EXPANSION OF THE CITY OF MANAUS, AMAZONAS, USING SATELLITE IMAGES - Alves, André Campos; Freitas, Ingrid Silva de; Santos, Mayara Queiroz dos (Geosaberes; Vol 11 (2020): Vol 11 (2020), 2020)
The present work approaches the use and occupation of land in the city of Manaus - AM, thus, orbital images were used that show the evolution of the event. The term (use and occupation) can be understood as the way in which space is being occupied by man, which has occurred since the beginning of human life. Man is a transforming agent and modifier of space, through the use of elements of nature, which serve for its survival. In Manaus, the anthropic actions and changes in the landscape stood out from two moments: Rubber Cycle and Manaus Free Trade Zone. Although these events occurred in different times, they contributed to population growth and brought changes in the way of use and the way of occupying urban land.